Area-Wide Control of Insect Pests From Research to Field Implementation - Vreysen, M. J. B.; Robinson, A. S.; Hendrichs, J.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2007)
"If major advances are to be made in coping with most of the major arthropod pest problems, then the tactics and strategies for managing such insects, ticks and mites must change. They must change from the current, limited scale, reactive, broad-spectrum measures to preventive measures that are target-pest specific and rigidly applied on an area-wide basis." E.F. Knipling on the occasion of receiving the World Food Prize on 12 October 1992.
Setting The Scene -- Basic Research -- Modelling and Methods Development -- Feasibility Studies -- Commercialization and Regulation -- Pilot Programmes -- Operationalaw-Ipm Programmes -- Lessons Learned.
Keywords: LIFE SCIENCES; AGRICULTURE; PLANT DISEASES; ENTOMOLOGY; LIFE SCIENCES; ENTOMOLOGY; AGRICULTURE; PLANT PATHOLOGY